Safety and immunogenicity of inactivated Fowl adenovirus serotype 8b isolate following different inactivation time intervals in broiler chickens - Mohamed Sohaimi, N.; Mohammad Azreen, A. Q.; Bejo, M. H.; Abd Rahaman, N. Y. (Razi Vaccine and Serum Research Institute, 2024)
In recent years, significant attention has been directed towards the development of inactivated fowl adenovirus (FAdV) vaccines within the poultry industry to combat outbreaks of inclusion body hepatitis (IBH). This study aimed to assess the safety and immunogenicity of an inactivated FAdV vaccine following different inactivation time intervals in commercial broiler chickens. The FAdV isolate UPM1137 was treated with binary ethyleneimine (BEI) at intervals of 20, 24, 28, 32, and 36 hours. All treated isolates underwent safety testing in specific pathogen-free (SPF) chicken embryonated eggs (CEE), followed by safety and immunogenicity trials in SPF chickens. The findings demonstrated that isolates treated at 20, 24, and 28 hours induced over 80% mortality in SPF CEE, while no mortality was observed in isolates treated at 32 and 36 hours. In SPF chickens, there were no clinical signs or gross and histological lesions recorded throughout the trial for those inoculated with isolates treated at 32 and 36 hours, indicating that these treatments rendered the virus completely inactivated and safe for use in commercial broiler chickens. Based on ELISA results, chickens vaccinated with the inactivated FAdV at 32 hours (group B) exhibited a higher antibody response compared to those vaccinated with the inactivated FAdV at 36 hours (group A) at days 14 and 28 post-inoculation (pi). At day 28 pi, the mean antibody titers for the booster groups in both group A and group B were significantly higher (p < 0.05) compared to the control group. These results indicate that both FAdV vaccines, using inactivated inocula at 32 and 36 hours, are safe and immunogenic in broiler chickens, particularly by day 28 pi following booster vaccination. Thus, it was concluded that the optimal duration for FAdV inactivation is 32 hours, making it highly suitable for future vaccine formulations.